Organ preservation in rectal cancer: a synopsis of current guidelines. (1st March 2018) - Borstlap, W. A. A.; van Oostendorp, S. E.; Klaver, C. E. L.; Hahnloser, D.; Cunningham, C.; Rullier, E.; Bemelman, W. A.; Tuynman, J. B.; Tanis, P. J.; ,
Abstract: Aim: The high morbidity associated with radical resection for rectal cancer is an incentive for surgeons to adopt strategies aimed at organ preservation, particularly for early disease. There are a number of different approaches to achieve this. In this study we have collated current national and international guidelines to produce a synopsis to support this changing practice. Method: The PubMed, Embase, Trip, National Guideline Clearinghouse and BMJ Best Practice databases were interrogated. Guidelines published before 2010 were excluded. The AGREE‐II tool was used for quality assessment. Results: Twenty‐four guidelines were drawn from 2278 potential publications. A consensus exists for local excision for 'low‐risk' T1 rectal cancer but there is no agreement on how to stratify the risk of treatment failure. There is a low level of agreement for rectal preservation for more advanced disease, but when mentioned it is recommended for unfit patients or in the context of a clinical trial. Guidelines are inconsistent with respect to surveillance in node‐negative disease and after complete response to chemoradiotherapy. Conclusion: According to current guidelines and consensus statements, organ preservation for rectal cancer beyond low‐risk T1 is still considered experimental and only indicated in patients who are unsuitable for radical surgery. Follow‐up strategies and cN0 staging deserve attention, highlighting the need for high‐quality clinical trials.